Effects of curcumin on metabolic and systemic diseases: Narrative review - Cruz-Bacilio, Wendy Fiorella (2025)
In recent years, the great role of nutrition on general health has been demonstrated, specifically, polyphenols in relation to the treatment of metabolic and systemic diseases. Curcumin, a substance extracted from turmeric and proposed as a treatment for various diseases due to its diverse properties. The bibliographic search was done in both Spanish and English with the keywords: "curcumin", "metabolic diseases", "systemic diseases" in Pubmed, Embase and Cochrane and Scholar Google. Curcumin is a polyphenol found in turmeric, which has been shown to have antioxidant, anti-inflammatory, hepatoprotective and antidiabetic properties. Its influence has been seen in metabolic syndrome, type 2 diabetes mellitus, lupus, rheumatoid arthritis and psoriasis. Conclusions: This narrative review summarizes the influence of curcumin supplementation on various pathologies, in addition to certain general aspects.